2020
DOI: 10.1103/physreva.102.013711
|View full text |Cite
|
Sign up to set email alerts
|

Quantum information preserving computational electromagnetics

Abstract: We propose a new methodology, called numerical canonical quantization, to solve quantum Maxwell's equations useful for mathematical modeling of quantum optics physics, and numerical experiments on arbitrary passive and lossless quantum-optical systems. It is based on: (1) the macroscopic (phenomenological) electromagnetic theory on quantum electrodynamics (QED), and (2) concepts borrowed from computational electromagnetics. It was shown that canonical quantization in inhomogeneous dielectric media required def… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 71 publications
0
31
0
Order By: Relevance
“…Many previous theoretical works [2,17,18] showed that, in principle, the concept of the standard canonical quantization in the vacuum can be extended to that of inhomogeneous and anisotropic lossless media once normal modes of the systems are properly found even though their closed form solutions are often restricted due to the geometrical complexity. As an effective solution to such difficulty, for the first time, we recently proposed in Reference [36] the so-called numerical canonical quantization in which normal modes are numerically obtained by solving the Helmholtz wave equations for arbitrary inhomogeneous dielectric media through computational electromagnetic (CEM) tools such as finite-difference or -element methods.…”
Section: Numerical Canonical Quantizationmentioning
confidence: 99%
See 4 more Smart Citations
“…Many previous theoretical works [2,17,18] showed that, in principle, the concept of the standard canonical quantization in the vacuum can be extended to that of inhomogeneous and anisotropic lossless media once normal modes of the systems are properly found even though their closed form solutions are often restricted due to the geometrical complexity. As an effective solution to such difficulty, for the first time, we recently proposed in Reference [36] the so-called numerical canonical quantization in which normal modes are numerically obtained by solving the Helmholtz wave equations for arbitrary inhomogeneous dielectric media through computational electromagnetic (CEM) tools such as finite-difference or -element methods.…”
Section: Numerical Canonical Quantizationmentioning
confidence: 99%
“…In a periodic vacuum box, there is an arbitrarily-shaped inhomogeneous dielectric object. To extract traveling-wave normal modes of the system, we use Bloch-periodic boundary condition instead of periodic boundary condition under which only standing-wave normal modes can exist [36].…”
Section: Numerical Canonical Quantizationmentioning
confidence: 99%
See 3 more Smart Citations